La violence indirecte : une recension des écrits avec des implications pour le milieu scolaire primaire - Verlaan, Pierrette; Besnard, Thérèse (Canadian Journal of Education/Revue canadienne de l’éducation, 2014)
This article provides an overview on three issues related to indirect aggression with the aim of making this information relevant for school settings. In particular,(a) do age and gender influence the development and persistence of indirectaggression?, (b) Do school staff’s perceptions and reactions to reports of indirect aggression contribute to its persistence or decline, and if so, how? (c) which evaluation methods are most likely to detect student involvement in this form of violence? The discussion puts forth possible solutions likely to influence the prevention of indirect aggression by identifying some of the most promising strategies for elementary schools.